Eye makeup system using interactive genetic algorithm - Chua,, Suk Ju. (Universiti Malaysia Sarawak, UNIMAS, 2010)
Eyes makeup is important to transform face and to i mprove eyes’ appearance in terms of colour and shape. When applying eyes makeu p, it is necessary to chose colours that suit to user’s appearance and preferen ce towards the colour. But, if user have ambiguous image for eyes makeup, it is ha rd to show the favourite and preferred colours of user’s eyes makeup. In order t o solve this problem, an eye makeup system using interactive Genetic Algorithm ( iGA) is proposed. This project focuses on the design and development of an eye makeup system using interactive Genetic Algorithm. This system is devel oped using Microsoft Visual Basic 6. This proposed system is to form an eye mak eup with colours that suit user’s taste, preference as well as emotion. The sy stem was developed based-on the concept of iGA that provides interaction betwee n user and system. Interaction is required for user to determine the fitness funct ions used in Genetic Algorithm. Implementation of the system shows the effectivenes s of the proposed system in generate eye makeup with colour that suit user pref erence.